Knowledge, Attitudes and Beliefs Regarding Drug Abuse among Male of Rural Community, Lahore, Pakistan - Masih, Orung Zaib; Hussain, Muhammad; Afzal, Muhammad; Emanual, Safina (International Journal of Social Sciences and Management, 2019)
Substance mishandle in Pakistan is one of the real reasons for worry that influences all sections of society. It has not just destroying consequences for the physical and mental prosperity yet in addition has the unfriendly impacts on labor and financial development of the nation. Roughly 6.7S million peoples in Pakistan have been related with various sorts of prescriptions. For instance, Cannabis is the most frequently used solution, with an inescapability of 3.6% of the people, after that poly-calm use is ordinary. With reference to sedatives, a normal 860,000 masses are general heroin customers and 320,000 are opium. Methods: The quantitative cross sectional study was used. Results: The discoveries of the examination. in 23 tables and 27 figures have been utilized to demonstrate comes about. That just about 80 for every penny of respondents viewed every single illicit medication as similarly hurtful to one's wellbeing recommend an inability to perceive the distinctive different impacts related with various medication writes (Cocaine, Grass, and Heroin). More than 94 for every penny of respondents announced that they had known about cannabis, and the larger part of respondents detailed having known about bliss (96.3%), cocaine (96.4%) and heroin (92.3%). Conclusions: The knowledge, attitude, and beliefs of drug abuse among male are good.